"Jihad now" vs. "Jihad later" : different means, same end - Navhat Nuraniyah (2014)
Indonesian jihadists are divided between those who insist on conducting “jihad now” and those advocating for “jihad later”. The division seems to stem from their disagreement about legitimate means of jihad but not from their religio-political goals.